2022
DOI: 10.1172/jci.insight.152012
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic 4R tau expression drives astrocyte reactivity and dysfunction

Abstract: The protein tau and its isoforms are associated with several neurodegenerative diseases, many of which are characterized by greater deposition of the 4R tau isoform; however, the role of 4R tau in disease pathogenesis remains unclear. We created antisense oligonucleotides (ASOs) that alter the ratio of 3R:4R tau to investigate the role of specific tau isoforms in disease. Preferential expression of 4R tau in human tau (hTau)-expressing mice was previously shown to increase seizure severity and phosphorylated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 70 publications
(105 reference statements)
1
13
0
Order By: Relevance
“…However, this finding is based on bulk transcriptomic data from wild-derived mouse strains. An increasing amount of work is currently going into identifying disease- and context-specific glial states (Keren-Shaul et al, 2017, Paolicelli et al, 2022, Ezerskiy et al, 2022). Single cell RNA sequencing will be necessary to better understand which microglia cell types are involved in this phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding is based on bulk transcriptomic data from wild-derived mouse strains. An increasing amount of work is currently going into identifying disease- and context-specific glial states (Keren-Shaul et al, 2017, Paolicelli et al, 2022, Ezerskiy et al, 2022). Single cell RNA sequencing will be necessary to better understand which microglia cell types are involved in this phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…to acquire neuroprotective and deleterious signatures in response to tau in PS19 mice and Aβ pathology in APP/PS1 mice [86]. Tau induced reactive astrocytes and loss of their neurosupportive functions in mouse models, including PS19, Thy-Tau22, hTau and rTgTauEC mice [52,[103][104][105][106][107][108]. Astrogliosis in turn could increase tau hyperphosphorylation and aggregation [109].…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 74 Interestingly, a recently published study demonstrated that the manipulation of tau splicing toward more 4R tau promotes a neurotoxic astrocyte phenotype characterized by the upregulation of C3 levels. 19 Conversely, under certain stimuli, astrocytes can upregulate the expression of many neurotrophic factors that promote the survival and growth of neurons and thrombospondins, which promote synapse repair. 75 Thus, subtypes of astrocytes might have beneficial or reparative functions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that lowering tau levels in 4R tau-expressing iPSC-derived astrocytes improves neuronal survival. 19 Thus, we aimed to determine if the deletion of astrocytic tau protects synapses against the toxic effects of Aβ oligomers.…”
Section: Introductionmentioning
confidence: 99%